Peran Pendidikan Islam Dalam Menanamkan Kesadaran Hak Dan Kewajiban Warga Negara - Soviyuddin Alhuliyi; Syamzaimar Syamzaimar (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
Islamic education has an important role in shaping citizens who are aware of their rights and obligations in social, national, and religious life. This study aims to analyze the role of Islamic education in instilling awareness of the rights and obligations of citizens and to identify factors that support the implementation of these values in everyday life. This research uses a qualitative approach through literature study by examining books, journals, and relevant scientific articles related to Islamic education and civic awareness. The results show that Islamic education contributes significantly in developing attitudes of responsibility, justice, discipline, tolerance, and obedience to the law. Islamic educational values also encourage individuals to understand the balance between rights and obligations as part of moral and social responsibility. In addition, teachers, family, and educational environments have an important role in strengthening civic awareness among students. Therefore, Islamic education can become a strategic means in forming citizens who are responsible, ethical, and have a strong national spirit.